Working memory and inhibitory control deficits in children with ADHD: an experimental evaluation of competing model predictions - Kofler, Michael J.; Groves, Nicole B.; Chan, Elizabeth S. M.; Marsh, Carolyn L.; Cole, Alissa M.; Gaye, Fatou; Cibrian, Enrique; Tatsuki, Miho O.; Singh, Leah J. (Frontiers in Psychiatry, 2024)
Introduction Children with ADHD demonstrate difficulties on many different neuropsychological tests. However, it remains unclear whether this pattern reflects a large number of distinct deficits or a small number of deficit(s) that broadly impact test performance. The current study is among the first experiments to systematically manipulate demands on both working memory and inhibition, with implications for competing conceptual models of ADHD pathogenesis. Method A clinically evaluated, carefully phenotyped sample of 110 children with ADHD, anxiety disorders, or co-occurring ADHD+anxiety (Mage=10.35, 44 girls; 69% White Not Hispanic/Latino) completed a counterbalanced, double dissociation experiment, with two tasks each per inhibition (low vs. high) x working memory (low vs. high) condition. Results Bayesian and frequentist models converged in indicating that both manipulations successfully increased demands on their target executive function (BF10>5.33x108, p<.001). Importantly, occupying children’s limited capacity working memory system produced slower response times and reduced accuracy on inhibition tasks (BF10>317.42, p<.001, d=0.67-1.53). It also appeared to differentially reduce inhibition (and non-inhibition) accuracy for children with ADHD relative to children with anxiety (BF10=2.03, p=.02, d=0.50). In contrast, there was strong evidence against models that view working memory deficits as secondary outcomes of underlying inhibition deficits in ADHD (BF01=18.52, p=.85). Discussion This pattern indicates that working memory broadly affects children’s ability to inhibit prepotent tendencies and maintain fast/accurate performance, and may explain the errors that children with ADHD make on inhibition tests. These findings are broadly consistent with models describing working memory as a causal mechanism that gives rise to secondary impairments. In contrast, these findings provide evidence against models that view disinhibition as a cause of working memory difficulties or view working memory as a non-causal correlate or epiphenomenon in ADHD.